Virulence and Genomic Feature of a Virulent Klebsiella pneumoniae Sequence Type 14 Strain of Serotype K2 Harboring blaNDM–5 in China - Mei, Yan-fang; Liu, Pan-pan; Wan, La-Gen; Liu, Yang; Wang, Lian-hui; Wei, Dan-dan; Deng, Qiong; Cao, Xian-wei (Frontiers in Microbiology, 2017)
The objective of this study was to reveal the molecular mechanism involved in carbapenem resistance and virulence of a K2 Klebsiella pneumoniae clinical isolate 24835. The virulence of the strain was determined by in vitro and in vivo methods. The denovo whole genome sequencing technology and molecular biology methods were used to analyze the genomic features associated with the carbapenem resistance and virulence of K.pneumoniae 24835. Strain 24835 was highly resistant to carbapenems and belonged to ST14, exhibited hypermucoviscous and unique K2-aerobactin-kfu-rmpA positive phenotype. As the only carbapenemase gene in strain 24835, blaNDM-5 was located on a 46-kb IncX3 self-transmissible plasmid, which is a very close relation of pNDM-MGR194 from India. Genetic context of blaNDM-5 in strain 24835 was closely related to those on IncX3 plasmids in various Enterobacteriaceae species in China. The combination of multiple virulence genes may work together to confer the relative higher virulence in K.pneumoniae 24835. Significantly increased resistance to serum killing and mice mortality were found in the virulent NDM-producing K.pneumoniae strain compared to the other NDM-producing K.pneumoniae strain. Our study provides basic information of phenotypic and genomic features of K.pneumoniae 24835, a strain displaying carbapenem resistance and relatively high level of virulence. These findings are concerning for the potential of NDM-like genes to disseminate among virulent K. pneumoniae isolates.